Shotgun metagenomic analysis of microbial communities in the surface waters of the Eastern South China Sea - Aazani, Mujahid; Jessica, Song; Lim, Po-Teen; Azizan, Abu Samah; Quack, Birgit; Pfeilsticker, Klaus; Tang, Sen-Lin; Ivanova, Elena; Müller, Moritz (Malaysian Society for Microbiology, 2017)
Aims: The South China Sea (SCS) harbours a rich biodiversity. However, few studies have been published on its diverse communities, particularly its microbial counterparts. As key players behind many of the vital processes carried out in the ocean, microbes are the focus of this study, placing particular emphasis on community composition, structure, and function. Methodology and results: By employing next generation shotgun sequencing technologies (Illumina HiSeq2000), we assessed the taxonomic structure and functional diversity of the prokaryotic communities in surface waters collected from 3 representative sites in the Eastern SCS: Sarawak (Kuching), Sabah (Kota Kinabalu), and Philippines (Manila). Comparisons were undertaken to similar studies from coastal and open ocean environments. All 3 locations were dominated by members of the Proteobacteria (Alpha- and Gamma-) and Cyanobacteria (Synechococcus sp. and Prochlorococcus sp.). The highest proportion of Gammaproteobacteria was found in Sarawak, representing an approximate 20% of total sequences. Archaeal assemblages were made up largely of Euryarchaeota and unclassified sequences, while Crenarchaeota and Thaumarchaeota were present in much smaller proportions, except in the Philippines where Thaumarchaeota made up almost 40% of the entire taxa. Conclusion, significance and impact of study: The majority of the microbial communities adhered to a core set of functional genes across the different locations. However, differences existed particularly in Sarawak waters which are hypothesized to be due to local environmental parameters such as riverine influence. The results obtained from this study provide the first comparison of prokaryotic communities in the surface waters of the eastern SCS and will serve as a good platform for prospective studies in the field of environmental science.